The Implementation of Mix-Pair-Share Strategy in Teaching Speaking Skill at School Amid Covid-19 Pandemic - Kamarudin Kamarudin (Cordova Journal : languages and culture studies, 2021)
This study is aimed at finding out the effectiveness of Mix Pair Share Strategy in teaching speaking skill at school. The study was an experimental design. The number of the sample was 48 students taken from the total number of the population which consisted of 176 students. Meanwhile, it was taken through cluster random sampling technique. The sample was also divided into two groups; experimental and control group. Each group was treated by different treatment; Mix Pair Share Strategy for the experimental group and Discussion method for the control group. The data of this study was collected through pre-test and post-test. The collected data then analyzed thoroughly. It was found that the mean score of experimental groups was higher than the score of control group (11.83>8.88), the deviation score of experimental groups was higher than the deviation of control group (2.96>2.83), and the value of t-test is higher than t-table, where t-test 5.88> t-table 2.000 for confidence level 0.05. Therefore, it is concluded that the implementation of Mix-Pair Share Strategy in teaching speaking skill at school amid Covid-19 pandemic was effective.